On If and Whether Complement Clauses of ‘See’, ‘Wonder’, and ‘Know’ in Contemporary Spoken Academic American English: A Corpus-Based Study - Gawlik, Oskar (Respectus Philologicus, 2013)
The main goal of this article is to investigate the distribution of two apparently vying finite complementation patterns—if and whether clauses—accompanying three mental verbs (see, wonder, and know) in the MICASE corpus of spoken academic American English. The default introspective theoretical assumption that the two investigated complementizers are in a free distribution was not corroborated by the empiricical inquiry. The three verbs do evince linguistic preferences regarding complementation, preferences which depend on a number of factors: the valency pattern of a given verb, co(n)text, sub-genre, and the like. Moreover, the investigation also appears to have demonstrated that, in respect to the complementation of see, wonder, and know, spoken academic English bears a greater resemblance to everyday conversation than to written academic English, thus corroborating the contention that field prevails over mode (to employ Hallidayan parlance). Furthermore, the inquiry into the semantics of the three mental verbs investigated indicates that their meanings are affected by the genre, inasmuch as the verbs investigated tend to depart from their default dictionary definitions by conveying less-prototypical meanings. This finding, in turn, provides a rationale for probing into the pragmatics and functions of the three verbs. It must be stressed that the results should not be generalised due to the relatively small corpus size, which implies that further research is indicated.
Keywords: See; Wonder; Know; If and Whether Complement Clauses; Complementation; Spoken Academic Discourse